2023
DOI: 10.1111/mmi.15108
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the disulfide stress response by the Bacillus subtilis Spx system at a single‐cell level

Abstract: To survive under adverse and fluctuating conditions, bacteria have evolved several mechanisms that sense and respond to stress. In the gram-positive bacterium Bacillus subtilis, the Spx protein (encoded by spxA) is a global transcriptional regulator controlling the expression of large number of genes in response to oxidative stress triggered by thiol-specific agents (Nakano et al., 2003;Rochat et al., 2012).Recent studies have shed light on the role of Spx in responding to other stressors, such as heat shock a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(114 reference statements)
1
0
0
Order By: Relevance
“…Intracellular PA dynamics were tracked microscopically after inducing PA formation in exponential PS832 amyE::P Hyperspank gfp(Sp)-cI78 EP8 cultures and subsequently monitoring growing cells on IPTG-free nutrient-poor agarose pads to trigger sporulation. As such, and in agreement with recent findings of Matavacas et al (2023) [ 26 ], we first observed that during vegetative growth B. subtilis PAs clearly adhered to the E. coli paradigm of nucleoid-enforced polar localization and asymmetric segregation during vegetative growth ( Figure 2 ). Interestingly, during subsequent sporulation, we could observe that PAs in sporulating cells became highly mobile and sampled more of the cytoplasmic environment, presumably due to an increase in nucleoid-free space as a result of the chromosome condensing into an axial filament during the early stages of sporulation [ 27 ].…”
Section: Resultssupporting
confidence: 93%
“…Intracellular PA dynamics were tracked microscopically after inducing PA formation in exponential PS832 amyE::P Hyperspank gfp(Sp)-cI78 EP8 cultures and subsequently monitoring growing cells on IPTG-free nutrient-poor agarose pads to trigger sporulation. As such, and in agreement with recent findings of Matavacas et al (2023) [ 26 ], we first observed that during vegetative growth B. subtilis PAs clearly adhered to the E. coli paradigm of nucleoid-enforced polar localization and asymmetric segregation during vegetative growth ( Figure 2 ). Interestingly, during subsequent sporulation, we could observe that PAs in sporulating cells became highly mobile and sampled more of the cytoplasmic environment, presumably due to an increase in nucleoid-free space as a result of the chromosome condensing into an axial filament during the early stages of sporulation [ 27 ].…”
Section: Resultssupporting
confidence: 93%